Topical virgin red palm oil improved wound healing by increasing fibroblasts, neovascularization and epithelialization in male Wistar rats (Rattus norvegicus) - Heidy Dwi Nadia; I Wayan Weta; I Gusti Made Aman (Fakultas Kedokteran Universitas Udayana, 2020)
Background: The healing process of burns wound can be accelerated using natural compound and one example of alternative medicine is virgin red palm Oil (VRPO). However, scientific evidence that back this notion is still lacking. Therefore, this study aimed to assess the effect VRPO toward burn wound healing in male wistar rats (Rattus norvegicus). Methods: An experimental randomized post-test only control group study was conducted using 28 male Wistar rats. Burn wound was created in all rats but only treatment group received VRPO while the control group was treated with placebo cream. Skin sample was obtained from each rat at day 4 and 11 for histological examination (fibroblasts density, neovascularization, and epithelialization). Results: The results showed that VRPO improved fibroblast density, neovascularization, and epithelialization at day 4 compared to control group. However, at day 11, there was a decreased in fibroblast density and neovascularization while epithelialization continuously increased at double the rate of the control group. Conclusion: Topical VRPO improved burn wound healing by increasing wound healing speed and epithelialization.